2014
DOI: 10.1002/14651858.cd008261.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological interventions for prevention or treatment of postoperative pain in people undergoing laparoscopic cholecystectomy

Abstract: Pharmacological interventions for prevention or treatment of postoperative pain in people undergoing laparoscopic cholecystectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 89 publications
0
18
0
3
Order By: Relevance
“…Gurusamy K in a 2014 Cochrane meta-analysis [6] studied the various pharmacological interventions for prevention or treatment of postoperative pain in people undergoing laparoscopic cholecystectomy. The authors found that the pain at 4 to 8 hours was generally reduced by about 1 to 2 cm on the visual analogue scale of 1 to 10 cm in the comparisons involving the different pharmacological agents and inactive controls.…”
Section: Difference In Pain Scoresmentioning
confidence: 99%
“…Gurusamy K in a 2014 Cochrane meta-analysis [6] studied the various pharmacological interventions for prevention or treatment of postoperative pain in people undergoing laparoscopic cholecystectomy. The authors found that the pain at 4 to 8 hours was generally reduced by about 1 to 2 cm on the visual analogue scale of 1 to 10 cm in the comparisons involving the different pharmacological agents and inactive controls.…”
Section: Difference In Pain Scoresmentioning
confidence: 99%
“…Preoperative sedation with midazolam hydrochloride and the routine analgesic regimen (intraoperative diclofenac and acetaminophen with metamizole in the early postoperative period) used in our institution was equivalent and sufficient for all the patients in each group where we did not detect any significant difference between postoperative pain scores. The use of perioperative intravenous narcotics was favored in two recent pediatric series for better compliance but opioids were reported to have serious adverse effects (11,12,20,21). Agarwal and Bagdi (10) used a bilateral subcostal transversus abdominis plane block under ultrasound guidance with similar pain scores to those of our study group.…”
Section: Discussionmentioning
confidence: 85%
“…In this regard, the Cochrane review had Fig. 2 Bar chart of the counts of other side effects (excluding sedation and nausea/vomiting) over time (hours) by group recommended quality of recovery measures instead to be assessed as outcomes for future studies [1].…”
Section: Discussionmentioning
confidence: 99%
“…Early postoperative pain is a common complaint after elective laparoscopic cholecystectomy, and persistent acute postoperative pain is the dominating complaint and the primary reason for prolonged stay after this procedure [1][2][3]. The mainstay of treatment for post-surgical pain involves the use of opioids.…”
Section: Introductionmentioning
confidence: 99%